Groebke‐Blackburn‐Bienaymé Multicomponent Reaction Catalysed by Reusable Brønsted‐Acidic Ionic Liquids. Issue 40 (1st October 2022) - Anjos, Nicolas S.; Chapina, Agáta I.; Santos, Ana R.; Licence, Peter; Longo, Luiz S.
Abstract: In the present work, the use of Brønsted acidic ionic liquids (BAIL) as catalysts for Groebke‐Blackburn‐Bienaymé (GBB) multicomponent reactions was systematically investigated. A series of four 1‐(butyl‐4‐sulfonic)‐3‐methylimidazolium salts bearing different anions was easily prepared and screened as acidic catalysts for this transformation. The best reaction conditions were stablished as 20 mol % of catalyst [(SO3 H) 4 C4 C1 Im][OTf] in refluxing EtOH or MeOH under conventional heating and in sealed tube at 150 °C for 1–4 hours under microwave heating, affording a series of imidazo‐fused heterocycles in moderate to excellent yields (42–93 %). The homogeneous BAIL catalyst could be recycled and reused in four consecutive reaction cycles, despite of a laborious recovery procedure employed. This approach represents the first example of a task‐specific reusable homogeneous Brønsted acidic catalyst in GBB reactions and opens new opportunities for the exploration of acidic ionic liquid phases as catalysts for this fascinating multicomponent reaction. Abstract : Groebke‐Blackburn‐Bienaymé multicomponent reactions can be efficiently catalysed by Brønsted acidic ionic liquids for the synthesis of imidazo[1, 2‐ a ]pyridines and imidazo[2, 1‐ b ]thiazoles in moderate to excellent yields (42–93 %), either under thermal or microwave heating. The homogeneous acidic catalyst can be recycled and reused in four consecutive reaction cycles.